Assessing consumers' preferences and willingness to pay for novel sliced packed fresh pears: A latent class approach. Issue 2 (19th November 2017) - Ikiz, Dila; Gallardo, R. Karina; Dhingra, Amit; Hewitt, Seanna
Abstract: The North American fresh pear industry faces marketing challenges that could jeopardize its' long‐term economic profitability. The production of sliced fresh pears is a promising alternative to overcome the lack of supplying consistently a product with superior quality with added convenience, potentially able to increase domestic consumption. In this paper, we used sensory evaluation and a Vickrey experimental auction to elicit consumers' preferences and willingness to pay for sliced packed fresh pears treated with SmartFresh™ (1‐methylcyclopropene) and subsequently with a ripening compound (RC) in the form of glyoxylic acid at different concentration levels (1%, 2%, 3%, and control). Panelists were willing to pay a price premium equivalent to 0.119/2 oz packet for the 2% RC sample, 0.055/2 oz packet for the 3% RC sample, and 0.025/2 oz packet for the 1% RC sample compared to the control sample. Results from a market segmentation analyses indicate the presence of two groups in the panelist sample. The group that liked sliced pears assigned higher importance to locally grown fruit and price, shopped at conventional retailer grocery stores, had fewer children in the household, and were younger compared to the group that disliked sliced pears. [EconLit citation: Q13].